Since `h` is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation.
Divide each term in the equation by `(7+5)` .
Divide each term in the equation by `2` .
You need to perform the multiplication to the right side, such that:
`144 = 2*7*h + 2*5*h`
`144 = 14h + 10h`
Performing the sum of the terms that contain the unknown h, yields:
`144 = 24h`
You need to evaluate h, hence, you need to divide by 24, such that:
`h = 144/24 => h = 6`
Hence, evaluating the value of `h, ` under the given conditions, yields `h = 6` .
We have to find h given 144 = 2h(7+5)
144 = 2h(7+5)
Simplify the terms within the brackets on the right hand side
144 = 2*h*12
Simplify the expression on the right hand side
144 = 24*h
Divide both the sides by 24
144/24 = (24*h)/24
6 = h
The solution of the equation is h = 6.